2023
DOI: 10.53801/jipki.v2i2.62
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Perawat dengan Motivasi Perawat dalam Pelaporan Insiden Keselamatan Pasien di RSUD Jakarta Tahun 2022

Abstract: Pendahuluan: Pelaporan insiden keselamatan pasien merupakan salah satu upaya untuk mengendalikan tingginya insiden keselamatan pasien. Pelaporan insiden keselamatan pasien di RSUD Sawah Besar selama tahun 2021 hanya terdapat 11 pelaporan insiden keselamatan pasien yang terdiri dari 7 kejadian tidak diharapkan (KTD 63,6%), 4 kejadian tidak cedera (KTC 36,3%). Tujuan: Untuk mengetahui hubungan pengetahuan perawat dengan motivasi perawat dalam pelaporan insiden keselamatan pasien di RSUD Sawah Besar Jakarta Tahun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…According to (Ulva, 2023), entitled "The Relationship between Nurse Knowledge and Nurse Motivation in Reporting Patient Safety Incidents at Sawah Besar Regional Hospital, Jakarta in 2022" states that the results of the research can be concluded regarding the description of nurses' knowledge regarding reporting patient safety incidents at Sawah Besar District Hospital, Jakarta in 2022. which is greater than half of 54.4%. The description of nurses' motivation in reporting patient safety incidents at Sawah Besar District Hospital, Jakarta in 2022 is low, namely greater than half of 50.9%.…”
Section: Resultsmentioning
confidence: 99%
“…According to (Ulva, 2023), entitled "The Relationship between Nurse Knowledge and Nurse Motivation in Reporting Patient Safety Incidents at Sawah Besar Regional Hospital, Jakarta in 2022" states that the results of the research can be concluded regarding the description of nurses' knowledge regarding reporting patient safety incidents at Sawah Besar District Hospital, Jakarta in 2022. which is greater than half of 54.4%. The description of nurses' motivation in reporting patient safety incidents at Sawah Besar District Hospital, Jakarta in 2022 is low, namely greater than half of 50.9%.…”
Section: Resultsmentioning
confidence: 99%